The Effect Of Price, Product, Service Quality, And Branding On Repurchase Intention Mediated By Customer Satisfaction Using SEM Tools Case Study: Food UMKM (Weekend Kitchen) - Nurardisa, Acyuta Intan; Waluyo, Minto (Dinasti International Journal of Economics, Finance & Accounting, 2025)
This study aims to determine the effect of price, product, and service quality on repurchase intention mediated by customer satisfaction at Weekend Kitchen Surabaya food UMKM. This research is motivated by the decline in the number of repeat purchases every year which is thought to be influenced by these factors. The research uses a quantitative method with a Structural Equation Modeling approach assisted by AMOS software. Respondents involved were 100 active customers who had purchased Weekend Kitchen products. The results showed that price and service quality have a significant effect on customer satisfaction, while product has no significant effect. Meanwhile, only price has a significant effect on repurchase intention, while product, service quality, and customer satisfaction show no significant effect. The conclusion of this study is that price is the main factor in shaping satisfaction and encouraging repeat purchases, so UMKM are advised to focus on pricing strategies that are in line with customer value perceptions, as well as evaluating product innovation and service strategies to increase customer loyalty.